Prevalence and factors associated with food insecurity among adults with HIV/AIDS treated at a referral hospital in Mozambique (Research, Society and Development, 2022)
Food insecurity is a public health problem due to its effects on the health of people infected with HIV, despite the undeniable benefits of antiretroviral treatment. The study aimed to analyze the prevalence and factors associated with food insecurity in people living with HIV/AIDS. This is a cross-sectional study, conducted with 206 patients seen, in May-July 2022. Socioeconomic, demographic, lifestyle and food security data were collected. Food insecurity was assessed using the Brazilian Scale of Food Insecurity, and its associations through Pearson's chi-square test/Fisher's exact test and prevalence ratio. The prevalence of food insecurity (severe) was higher in males (78.9%), aged 18-30 years (88.9%), with no level of education (82.4%), unemployed (72.3%), married (73.1%), in households of 4 to 6 members (77, 3%) and living in inadequate housing conditions (70.2%), with stage II disease (78.4%), non-smokers (71.9%), regular consumers of alcoholic beverages (73.7%) and practicing physical activity (76.4%). Statistical associations were found between food insecurity and age group (p = 0.001), education (p = 0.001), employment status (p < 0.011), number of people per household (p < 0.028), being a smoker (p < 0.013) and disease stage (p < 0.017). The results suggest that investments in policies aimed at improving agricultural production, income, education, access to employment and reduction of poverty levels are necessary to increase the availability, improved access and use of food.